Molecular Detection and Phylogeny of Anaplasma phagocytophilum and Related Variants in Small Ruminants from Turkey - Aktas, Munir; Ozubek, Sezayi; Ulucesme, Mehmet Can (Mdpi, 2021)
Simple Summary We explored the existence of Anaplasma phagocytophilum and related variant in samples of goats and sheep obtained from Antalya and Mersin provinces, representative of Mediterranean region of Turkey. Based on 16S rRNA and groEL genes of A. phagocytophilum and related variants, we examined blood samples by polymerase chain reaction (PCR) followed by sequencing. The results showed that the prevalence of A. phagocytophilum and A. phagocytophilum-like 1 infection was 1.4% and 26.5%, respectively. Sequencing confirmed molecular data and showed the presence of A. phagocytophilum and A. phagocytophilum-like-1 variant in the sampled animals. Anaplasma phagocytophilum causes tick-borne fever in small ruminants. Recently, novel Anaplasma variants related to A. phagocytophilum have been reported in ruminants from Tunisia, Italy, South Korea, Japan, and China. Based on 16S rRNA and groEL genes and sequencing, we screened the frequency of A. phagocytophilum and related variants in 433 apparently healthy small ruminants in Turkey. Anaplasma spp. overall infection rates were 27.9% (121/433 analyzed samples). The frequency of A. phagocytophilum and A. phagocytophilum-like 1 infections was 1.4% and 26.5%, respectively. No A. phagocytophilum-like 2 was detected in the tested animals. The prevalence of Anaplasma spp. was comparable in species, and no significant difference was detected between sheep and goats, whereas the prevalence significantly increased with tick infestation. Sequencing confirmed PCR-RFLP data and showed the presence of A. phagocytophilum and A. phagocytophilum-like-1 variant in the sampled animals. Phylogeny-based on 16S rRNA gene revealed the A. phagocytophilum-like 1 in a separate clade together with the previous isolates detected in small ruminants and ticks. In this work, A. phagocytophilum-like 1 has been detected for the first time in sheep and goats from Turkey. This finding revealed that the variant should be considered in the diagnosis of caprine and ovine anaplasmosis.
Keywords: tick-borne fever; Anaplasma phagocytophilum-like 1; PCR-RFLP; small ruminant